Spatial layout design factors during panic situations - Ibrahim, Najihah; Hassan, Fadratul Hafinaz (2017)
Crowd management is the human-traffic problem-solving for crowd control to manage the crowd activities by monitoring, simulating and designing model.This concept paper is to discuss on the crowd management and discover the major contributing factors that lead towards casualties during panic situation.Crowd management activity has a close relation with spatial management that gives a high impact towards the movement of pedestrian during a certain situation and space.Hence, this concept paper provides a validation on effect of the behavior reflection based on the spatial layout design during panic situation.